Prognostic value of KRAS mutation in patients undergoing pulmonary metastasectomy for colorectal cancer: A systematic review and meta-analysis. (April 2021) - Huang, Junfeng; Zang, Qing; Wen, Yaokai; Pan, Zhe; Yao, Zhiyuan; Huang, Mingkai; Huang, Jiongqiang; Chen, Jingsong; Wang, Rongchang
Graphical abstract: Highlights: KRAS mutation is a strong prognostic biomarker of poor survival after resection of colorectal lung metastases. Clinicopathological factors have significant impact on survival and recurrence after resection of colorectal lung metastases. A comprehensive predictive model is proposed for the optimal surgical candidate. Additional research is needed to explore how KRAS mutation influence prognosis of resectable colorectal lung metastases. Abstract: Background: The purpose of the study was to evaluate whether KRAS mutation could be an independent prognostic biomarker in patients undergoing pulmonary metastasectomy (PM) for colorectal cancer (CRC). Methods: A systemic review was performed by searching online databases to identify studies reporting overall survival (OS) and recurrence free survival (RFS) of CRC patients undergoing PM. Pooled HRs were calculated for OS and RFS. Results: A total of 15233 patients from 60 studies were included. Pooled analysis showed that KRAS mutation was associated with worse OS (HR: 1.86, 95 % Cl: 1.35–2.57) and RFS (HR: 1.68, 95 % Cl: 1.38–2.04). A significant effect on OS and/or RFS was also shown by other 18 factors. Conclusions: This meta-analysis found that KRAS mutation is an important prognostic predictor for OS and RFS in CRC patients undergoing PM, supporting a comprehensive model including clinicopathological and biological factors for optimal patients selection and prognosis for surgical treatment.